Preparation method of fat-soluble vitamin E powder
Through mechanochemical combining eutectics and inclusion technology, polymer materials and surfactants are used to improve the solubility of vitamin E, which solves the problem of insufficient stability and water solubility of vitamin E in the existing technology, and achieves an efficient and environmentally friendly industry Large-scale production.
Patent Information
- Application Number
- CN202411515528.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The prior art is difficult to effectively improve the stability and water solubility of fat-soluble vitamin E, and there are cost and technical challenges in industrial scale production, especially the continuous production of thermally sensitive raw materials is limited.
By combining mechanochemical method with eutectic and inclusion technology, the solubility of vitamin E is improved by combining with eutectic solvents and hydrogen bond receptors, and the solubility of vitamin E-proline is prepared by ball milling. Acid eutectic products further improve their water solubility and bioavailability.
It has achieved efficient, environmentally friendly and low-cost improvement in water solubility and bioavailability of fat-soluble vitamin E, provided new formulation development ideas, suitable for large-scale industrial production, and avoided the use of toxic solvents.
Smart Images

Figure CN119215198A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solubilization of poorly soluble drugs, and particularly relates to a method for preparing fat-soluble vitamin E powder. Background Art
[0002] Vitamins are a type of micronutrient that is essential to living organisms but cannot be synthesized by the organism itself and can only be taken in from the outside. It is known that many vitamins are effective coenzyme components of enzymes and play an indispensable role in human growth, metabolism, and development. Vitamin E, also known as tocopherol, is a fat-soluble vitamin. Natural vitamin E is a colorless or light yellow transparent oily liquid that is easily oxidized in the air and loses its activity, so it is often esterified. With the continuous deepening of research on the physical and chemical properties of vitamins, vitamins and their related derivatives are also receiving more and more attention in the fields of food, feed (about 200-300g of vitamin E is required in 1KG of feed), cosmetics (antioxidant effect), chemical industry, nutrition and health care, and pharmaceuticals.
[0003] However, most vitamins are unstable and easily lose their activity due to the catalysis of light, pH, temperature, metal ions, oxygen and other conditions. They are easily degraded during processing and storage. In particular, fat-soluble vitamins are usually poorly water-soluble during digestion, which further limits their clinical application. Therefore, vitamins are often encapsulated to obtain products with excellent physical and chemical properties. For example, they are prepared into dosage forms such as powders, injections, tablets, microcapsules, liposomes, etc. The preparation methods include spray drying, thin layer dispersion, emulsification, ultrasound, high-pressure homogenization, etc., and the above preparation technologies and processes have many limitations in terms of cost or expansion of production. The emergence of eutectic technology breaks through the barrier that fat-soluble vitamins usually need to be esterified first to achieve stability improvement. Low-cost small molecules such as amino acids are preferred to form drug eutectic products, which can achieve the change from oily substances to powdery states. Powdered products are limited in continuous production by not being applicable to heat-sensitive raw materials. Therefore, the prepared eutectic products can be prepared into inclusion compounds, which provides the possibility of further expanding the solubility, stability, bioavailability and other physical and chemical properties of drugs. In terms of preparation technology, mechanochemical technology is preferred, which not only saves costs, but also has advantages in sustainability and expanded production.
[0004] Patent CN118716499A discloses a method for preparing water-soluble vitamin E, which comprises dissolving vitamin E and β-cyclodextrin with an aqueous solution of xylitol and an aqueous solution of choline chloride, respectively, and then electrospinning the vitamin E-β-cyclodextrin inclusion complex after inclusion. The aqueous solution of xylitol can form a low eutectic solvent with choline chloride to promote the inclusion of vitamin E with β-cyclodextrin, and choline chloride acts as a hydrogen bond receptor to bind to β-cyclodextrin and xylitol, which can effectively weaken the intramolecular hydrogen bond and reduce the lattice energy, thereby further improving the solubility of vitamin E. However, this preparation method is suitable for laboratory pilot scale, and may encounter technical and economic challenges in industrial-scale production.
[0005] Patent CN114886122B discloses a method for preparing vitamin E powder, in which DL-α-tocopheryl acetate: silicon dioxide: PEG4000: PVP K90 with a mass ratio of 50:45:3:2 is added to a ball mill and sieved to complete the preparation of the powder. However, this research method does not improve the water solubility of vitamin E by much, and the esterification process also generates additional costs.
[0006] Since most vitamins are first converted into free forms in the body before being digested and absorbed, the cocrystal technology that can associate active drug ingredients with auxiliary drugs without changing the original covalent structure of the drug and only rely on weak interactions such as hydrogen bonds has entered the field of vision of researchers. Since API and CCF are bound together by weak interactions such as hydrogen bonds, they are easily decomposed into free forms by digestive enzymes after oral administration and enter the gastrointestinal tract, which is easy to absorb. A large number of literature studies have also shown that in vitro evaluation based on dissolution and / or solubility is sufficient to prove that API dissociates from CCF before reaching the pharmacological active site (Cryst. Growth Des. 2023, 23, 1-5) and becomes free form for digestion and absorption. Therefore, the development of vitamin cocrystal drugs is very necessary. However, the hot melt extrusion technology currently introduced for the continuous production of drug cocrystal products is limited by the inability to be applied to heat-sensitive raw materials, resulting in the current preparation of cocrystals still mainly based on intermittent production. To solve this problem, inclusion complexes can be prepared into cocrystals, which not only solve the problem of continuous production, but also the combination of the two technologies is expected to further improve drug solubility, bioavailability, stability, etc. Inclusion technology is an inclusion complex formed by a guest molecule being embedded in the cavity structure of another host molecule. Common host molecules include cyclodextrins, calixarene, cucurbituril, pillararene, etc. They have a relatively hydrophobic central cavity and a hydrophilic outer surface (Pharmaceuticals 2023, 16, 1074). This unique cavity structure can embed hydrophobic molecules of appropriate size.
[0007] Mechanochemical grinding is a more environmentally friendly, greener and sustainable technology, and has been named by the International Union of Pure and Applied Chemistry (IUPAC) as one of the innovative technologies with the potential to change the world. Etter et al.'s research showed that the experimental conditions of a large amount of solvent are not necessary for the formation of eutectics (Physical Chemistry, 1991, 95(12):4601-4610), which paves the way for the application of mechanochemistry in pharmaceutical eutectics. Similarly, eutectic inclusion compounds can also be prepared using mechanochemical methods. Summary of the invention
[0008] In view of the above problems, the present invention aims to prepare a method for preparing fat-soluble vitamin E powder. The method firstly starts from the research purpose, and the combination of eutectic and inclusion technology is expected to achieve the additive effect of the two methods; secondly, low-cost eutectic formers and encapsulation materials are selected; finally, the mechanochemical method is selected in the preparation process, which is more suitable for expansion and sustainable production than the solution method.
[0009] The specific technical solutions are as follows: A method for preparing fat-soluble vitamin E powder comprises the following steps: 1) Add vitamin E and a eutectic former into a ball mill, add a small amount of methanol, add zirconium oxide beads as a ball milling medium, seal it, and place it on a planetary ball mill for ball milling to obtain a vitamin E-proline drug eutectic product; 2) Adding the vitamin E-proline drug cocrystal product prepared in step 1), a surfactant, a flow aid and a polymer material into a ball mill, and then adding zirconium oxide beads as a ball milling medium. After sealing, the ball mill is placed on a planetary ball mill for ball milling to obtain a vitamin E powder product.
[0010] Furthermore, the eutectic former is proline, betaine, glutamic acid, nicotinamide, gallic acid, malonic acid or nicotinic acid, preferably proline or betaine; the surfactant is Tween-80, Span 60, poloxamer 188, monoglyceride, povidone K90 or sodium dodecyl sulfate, preferably poloxamer 188; the glidant is talc, silicon dioxide or magnesium stearate, preferably silicon dioxide; the polymer material is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-β-cyclodextrin, preferably hydroxypropyl-β-cyclodextrin.
[0011] Furthermore, in step 2), the mass feed ratio of vitamin E, eutectic former, surfactant, glidant and polymer material is 25%:3%:2%:2%:18%.
[0012] Furthermore, in step 2), the rotation speed of the ball mill is 100-300 rpm, preferably 250 rpm; and the ball milling time is 0.5-4 h, preferably 2 h.
[0013] Furthermore, the mass ratio of the zirconium oxide beads to the total material added is 5-30:1, and the filler of the ball mill is 10-30%, preferably 20%.
[0014] By adopting the above technology, compared with the existing technology, the beneficial effects of the present invention are embodied in: 1) The present invention uses polymer materials as carriers to increase the solubility of the drug, and uses surfactants and glidants to increase its dissolution rate, which is beneficial to improving the bioavailability of fat-soluble vitamin E in the body; 2) The present invention prepares 50% fat-soluble vitamin E powder by a limited preparation method, which is simple to operate and avoids the use of toxic and harmful organic solvents compared with traditional preparations, is more environmentally friendly, has the advantages of simple operation, low production cost, scalable production, environmental friendliness and no pollution, etc., and is a preparation method with broad application prospects; 3) The present invention prepares 50% fat-soluble vitamin E powder by mechanical force, prepares vitamin E and L-proline into drug co-crystals and ball-mills with polymer carriers, which can significantly improve the water solubility of fat-soluble vitamin E, and provides new ideas and methods for the development of feed powders in preparations; 4) The present invention innovatively combines eutectic technology with inclusion technology, and is expected to achieve the additive effect of the two methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Solubility graph of vitamin E powder prepared with different excipient and carrier formulations; Figure 2 This is the solubility diagram of vitamin E powder with different ball-to-material ratios; Figure 3 This is the solubility diagram of vitamin E powder with different ball milling times; Figure 4 This is the solubility diagram of vitamin E powder at different rotation speeds; Figure 5 This is the solubility diagram of vitamin E powder with different filling rates. DETAILED DESCRIPTION
[0016] The present invention is further described below in conjunction with specific embodiments and drawings of the specification, but the protection scope of the present invention is not limited thereto.
[0017] Example 1: Preparation of Vitamin E Pharmaceutical Cocrystal Product Using Proline as Cocrystal Former of Vitamin E Add vitamin E (4.8 g), L-proline (0.575 g), and 4 ml of methanol to a 50 ml tetrafluoroethylene ball mill. Add 36 g of 15 mm diameter zirconium oxide beads as grinding media, mix well, and put into a planetary ball mill. Set the speed to 250 rpm and the time to 2 hours. A powdery white solid with good fluidity is obtained.
[0018] Example 2: Preparation of 50% Vitamin E powder with Hydroxypropyl-β-cyclodextrin and Tween-80 as carriers (Vitamin E: L-proline: Tween-80: silicon dioxide: Hydroxypropyl-β-cyclodextrin = 25%: 3%: 2%: 2%: 18%) Add vitamin EL-proline eutectic (14g), Tween-80 (1g), silicon dioxide (1g), hydroxypropyl-β-cyclodextrin (9g) to a 300ml tetrafluoroethylene ball mill, add 380g of 15mm diameter zirconium oxide beads as grinding media, mix well and put into a planetary ball mill, set the speed to 250rpm, and the time to 2h. After the end, take an appropriate amount of product in a 50ml centrifuge tube, add 10ml of distilled water, cover the lid and place it in a constant temperature water bath oscillator at 37℃, and oscillate at 150rpm for 24 hours. Take the supernatant and pass it through a 0.45μm needle filter and use high performance liquid chromatography for analysis. The experimental results show that the solubility of vitamin E in this component is 154.37μg / mL.
[0019] Example 3: Preparation of 50% Vitamin E powder with hydroxypropyl-β-cyclodextrin and poloxamer 188 as carriers (Vitamin E: L-proline: poloxamer 188: silicon dioxide: hydroxypropyl-β-cyclodextrin = 25%: 3%: 2%: 2%: 18%) Vitamin E-proline cocrystal (14 g), poloxamer 188 (1 g), silicon dioxide (1 g), hydroxypropyl-β-cyclodextrin (9 g) were added to a 300 ml tetrafluoroethylene ball mill, and 380 g of 15 mm diameter zirconium oxide beads were added as grinding media. After mixing evenly, the mixture was placed in a planetary ball mill, and the speed was set to 250 rpm for 2 hours. After the mixture was finished, an appropriate amount of the product was placed in a 50 ml centrifuge tube, 10 ml of distilled water was added, the lid was closed, and the mixture was placed in a constant temperature water bath oscillator at 37 ° C, and oscillated at 150 rpm for 24 hours. The supernatant was filtered through a 0.45 μm needle filter and analyzed by high performance liquid chromatography. The experimental results showed that the solubility of vitamin E in this component was 178.35 μg / mL.
[0020] Example 4: Preparation of 50% Vitamin E powder with Hydroxypropyl-β-cyclodextrin and Span 60 as carriers (Vitamin E: L-proline: Span 60: Silicon dioxide: Hydroxypropyl-β-cyclodextrin = 25%: 3%: 2%: 2%: 18%) Vitamin E-proline eutectic (14 g), Span 60 (1 g), silicon dioxide (1 g), hydroxypropyl-β-cyclodextrin (9 g) were added to a 300 ml tetrafluoroethylene ball mill, and 380 g of 15 mm diameter zirconium oxide beads were added as grinding media. After mixing evenly, the mixture was placed in a planetary ball mill, and the speed was set to 250 rpm for 2 hours. After the mixture was finished, an appropriate amount of the product was placed in a 50 ml centrifuge tube, 10 ml of distilled water was added, the tube was covered, and the mixture was placed in a constant temperature water bath oscillator at 37 ° C, and oscillated at 150 rpm for 24 hours. The supernatant was filtered through a 0.45 μm needle filter and analyzed by high performance liquid chromatography. The experimental results showed that the solubility of vitamin E in this component was 116.96 μg / mL.
[0021] Example 5: Preparation of 50% Vitamin E powder with Hydroxypropyl-β-cyclodextrin and Povidone K90 as carriers (Vitamin E: L-proline: Povidone K90: Silicon dioxide: Hydroxypropyl-β-cyclodextrin = 25%: 3%: 2%: 2%: 18%) Vitamin E-proline eutectic (14 g), povidone K90 (1 g), silicon dioxide (1 g), hydroxypropyl-β-cyclodextrin (9 g) were added to a 300 ml tetrafluoroethylene ball mill, and 380 g of 15 mm diameter zirconium oxide beads were added as grinding media. After mixing evenly, the mixture was placed in a planetary ball mill, and the speed was set to 250 rpm for 2 h. After the mixture was finished, an appropriate amount of the product was placed in a 50 ml centrifuge tube, 10 ml of distilled water was added, the lid was closed, and the mixture was placed in a constant temperature water bath oscillator at 37 ° C, and oscillated at 150 rpm for 24 hours. The supernatant was filtered through a 0.45 μm needle filter and analyzed by high performance liquid chromatography. The experimental results showed that the solubility of vitamin E in this component was 45.93 μg / mL.
[0022] Example 6: Preparation of 50% Vitamin E powder with hydroxypropyl-β-cyclodextrin and monoglyceride as carriers (Vitamin E: L-proline: monoglyceride: silicon dioxide: hydroxypropyl-β-cyclodextrin = 25%: 3%: 2%: 2%: 18%) Add vitamin EL-proline eutectic (14g), monoglyceride (1g), silicon dioxide (1g), hydroxypropyl-β-cyclodextrin (9g) to a 300ml tetrafluoroethylene ball mill, add 380g of 15mm diameter zirconium oxide beads as grinding media, mix well and put into a planetary ball mill, set the speed to 250rpm, and the time is 2h. After the end, take an appropriate amount of product in a 50ml centrifuge tube, add 10ml of distilled water, cover the lid and place it in a constant temperature water bath oscillator at 37℃, and oscillate at 150rpm for 24 hours. Take the supernatant and pass it through a 0.45μm needle filter and use high performance liquid chromatography for analysis. The experimental results show that the solubility of vitamin E in this component is 70.31μg / mL.
[0023] Example 7: Preparation of 50% vitamin E powder with hydroxypropyl-β-cyclodextrin and sodium lauryl sulfate as carriers (vitamin E: L-proline: sodium lauryl sulfate: silicon dioxide: hydroxypropyl-β-cyclodextrin = 25%: 3%: 2%: 2%: 18%) Vitamin E-proline eutectic (14 g), sodium dodecyl sulfate (1 g), silicon dioxide (1 g), hydroxypropyl-β-cyclodextrin (9 g) were added to a 300 ml tetrafluoroethylene ball mill, and 380 g of 15 mm diameter zirconium oxide beads were added as grinding media. After mixing evenly, the mixture was placed in a planetary ball mill, and the speed was set to 250 rpm for 2 h. After the mixture was finished, an appropriate amount of the product was placed in a 50 ml centrifuge tube, 10 ml of distilled water was added, the tube was covered, and the mixture was placed in a constant temperature water bath oscillator at 37 ° C, and oscillated at 150 rpm for 24 hours. The supernatant was filtered through a 0.45 μm needle filter and analyzed by high performance liquid chromatography. The experimental results showed that the solubility of vitamin E in this component was 62.28 μg / mL.
[0024] Example 8: Preparation of 50% Vitamin E powder with β-cyclodextrin and poloxamer 188 as carriers (Vitamin E: L-proline: poloxamer 188: silicon dioxide: β-cyclodextrin = 25%: 3%: 2%: 2%: 18%) Vitamin E-proline cocrystal (14 g), poloxamer 188 (1 g), silicon dioxide (1 g), β-cyclodextrin (9 g) were added to a 300 ml tetrafluoroethylene ball mill, and 380 g of 15 mm diameter zirconium oxide beads were added as grinding media. After mixing evenly, the mixture was placed in a planetary ball mill, and the speed was set to 250 rpm for 2 hours. After the mixture was finished, an appropriate amount of the product was placed in a 50 ml centrifuge tube, 10 ml of distilled water was added, the tube was covered, and the mixture was placed in a constant temperature water bath oscillator at 37 ° C, and oscillated at 150 rpm for 24 hours. The supernatant was filtered through a 0.45 μm needle filter and analyzed by high performance liquid chromatography. The experimental results showed that the solubility of vitamin E in this component was 1.78 μg / mL.
[0025] In Example 2-8, Tween 80, Poloxamer 188, Span 60, Povidone K90, monoglyceride, and sodium lauryl sulfate were selected as surfactants, and hydroxypropyl-β-cyclodextrin or β-cyclodextrin was selected as a polymer material to prepare 50% vitamin E powders (50% means that the vitamin E content accounts for 50% of the total material) with different excipients, and the solubility of vitamin E in each powder was plotted into a curve, as shown in FIG. Figure 1 As shown, it is concluded that hydroxypropyl-β-cyclodextrin and poloxamer are preferred, and the solubility of vitamin E in the prepared powder is the highest, which is 178.35 μg / mL.
[0026] Example 9: Ball to Material Ratio Screening With the powder formulation in Example 3, add materials in a 300ml tetrafluoroethylene ball mill according to the ratio of vitamin EL-proline cocrystal: poloxamer 188: silicon dioxide: hydroxypropyl-β-cyclodextrin: = 25%: 3%: 2%: 2%: 18%, and add zirconium oxide beads with a diameter of 15mm as grinding media in a ball-to-material ratio of 5:1, 10:1, 15:1, 20:1, 30:1. After mixing evenly, put it into a planetary ball mill at a speed of 250rpm for 2h. After the end, take an appropriate amount of product in a 50ml centrifuge tube, add 10ml of distilled water, cover the lid and place it in a constant temperature water bath oscillator at 37°C, and oscillate at a speed of 150rpm for 24 hours. Take the supernatant and pass it through a 0.45μm needle filter and use high performance liquid chromatography for analysis. Figure 2 The experimental results show that when the ball-to-material ratio is 15:1, the solubility of vitamin E in this component is the highest, which is 170.21μg / mL.
[0027] Example 10: Ball milling time screening Using the powder formulation in Example 3, add vitamin EL-proline cocrystal (14 g), poloxamer 188 (1 g), silicon dioxide (1 g), hydroxypropyl-β-cyclodextrin (9 g) to a 300 ml tetrafluoroethylene ball mill, add 380 g of 15 mm diameter zirconium oxide beads as grinding media, mix well and put into a planetary ball mill. The five groups of experiments were set to a time of 30 min, 1 h, 2 h, 3 h, and 4 h, and a rotation speed of 250 rpm. After completion, take an appropriate amount of the product in a 50 ml centrifuge tube, add 10 ml of distilled water, cover the lid and place in a constant temperature water bath oscillator at 37 ° C, and oscillate at 150 rpm for 24 hours. Take the supernatant and pass it through a 0.45 μm needle filter and use high performance liquid chromatography for analysis. Figure 3 The experimental results show that the solubility of vitamin E in this component is the highest at 177.41 μg / mL after 2 hours of reaction.
[0028] Example 11: Ball milling speed screening Using the powder formulation in Example 3, add vitamin EL-proline cocrystal (14 g), poloxamer 188 (1 g), silicon dioxide (1 g), and hydroxypropyl-β-cyclodextrin (9 g) to a 300 ml tetrafluoroethylene ball mill, add 380 g of zirconia beads with a diameter of 15 mm as grinding media, mix well and put into a planetary ball mill. The five groups of experiments were set to rotate at 100 rpm, 150 rpm, 200 rpm, 250 rpm, and 300 rpm for 2 hours. After the end, take an appropriate amount of the product in a 50 ml centrifuge tube, add 10 ml of distilled water, cover the lid, and place in a constant temperature water bath oscillator at 37°C, and oscillate at 150 rpm for 24 hours. Take the supernatant and pass it through a 0.45 μm needle filter and use high performance liquid chromatography for analysis. Figure 4 The experimental results show that when the rotation speed is 250rpm, the solubility of vitamin E in this component is the highest, which is 185.41μg / mL.
[0029] Example 12: Ball mill filling rate screening With the powder formulation in Example 3, add vitamin EL-proline cocrystal: poloxamer 188: silicon dioxide: hydroxypropyl-β-cyclodextrin in a 300ml tetrafluoroethylene ball mill according to the ratio of 25%: 3%: 2%: 2%: 18%, add zirconium oxide beads with a diameter of 15mm as grinding media according to the filling rate of 10%, 15%, 20%, 25%, 30%, mix well and put into a planetary ball mill at a speed of 250rpm and a reaction time of 2h. After completion, take an appropriate amount of product in a 50ml centrifuge tube, add 10ml of distilled water, cover the lid and place in a constant temperature water bath oscillator at 37°C, and oscillate at a speed of 150rpm for 24 hours. Take the supernatant and pass it through a 0.45μm needle filter and use high performance liquid chromatography for analysis. Figure 5 ,The experimental results show that when the filling rate is 20%, the solubility of vitamin E in this component is the highest, which is 209.1μg / mL.
[0030] In Examples 9-12, different ball milling parameters were selected to screen the optimal solubility and prepare 50% vitamin E powder with different excipients. The optimal ball milling conditions were as follows: ball milling speed of 250 rpm, reaction time of 2 h, filling rate of 20%, and ball-to-material ratio of 15:1.
Claims
1. A method for preparing fat-soluble vitamin E powder, characterized in that: The steps include: 1) Add vitamin E and a eutectic former into a ball mill, add a small amount of methanol, add zirconium oxide beads as a ball milling medium, seal it, and place it on a planetary ball mill for ball milling to obtain a vitamin E-proline drug eutectic product; 2) Adding the vitamin E-proline drug cocrystal product prepared in step 1), a surfactant, a flow aid and a polymer material into a ball mill, and then adding zirconium oxide beads as a ball milling medium. After sealing, the ball mill is placed on a planetary ball mill for ball milling to obtain a vitamin E powder product.
2. The method for preparing a fat-soluble vitamin E powder according to claim 1, characterized in that: The eutectic former is proline, betaine, glutamic acid, nicotinamide, gallic acid, malonic acid or nicotinic acid, preferably proline or betaine; the surfactant is Tween-80, Span 60, poloxamer 188, monoglyceride, povidone K90 or sodium dodecyl sulfate, preferably poloxamer 188; the glidant is talc, silicon dioxide or magnesium stearate, preferably silicon dioxide; the polymer material is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin and hydroxypropyl-β-cyclodextrin, preferably hydroxypropyl-β-cyclodextrin.
3. The method for preparing a fat-soluble vitamin E powder according to claim 2, characterized in that: In step 2), the mass feed ratio of vitamin E, eutectic former, surfactant, flow aid and polymer material is 25%:3%:2%:2%:18%.
4. The method for preparing a fat-soluble vitamin E powder according to claim 1, characterized in that: The ball mill speed in step 2) is 100-300 rpm, preferably 250 rpm; the ball milling time is 0.5-4 h, preferably 2 h.
5. The method for preparing a fat-soluble vitamin E powder according to claim 1, characterized in that: The mass ratio of zirconium oxide beads to the total material added is 5-30:1, and the filler of the ball mill is 10-30%, preferably 20%.
Citation Information
Patent Citations
Drug-cyclodextrin nanoparticles and preparation method thereof
CN102008450A
Cocrystallization of tocopherol and proline as well as preparation method thereof
CN108033939A
Preparation method of water-soluble vitamin E
CN118716499A
